Pedagogical possibilities for developing cognitive competence of future teachers based on a facilitative approach - Rahmankulova, Nafisa (The Lingua Spectrum, 2025)
This article explores the pedagogical opportunities for developing the cognitive competence of future teachers through the facilitative approach. The relevance of the topic is driven by the growing demands for teacher training within the framework of the competence-based and digital education paradigms. The concept of “cognitive competence” is examined in detail, including its structure and significance in the professional activities of teachers. The article substantiates the effectiveness of the facilitative approach as an innovative pedagogical strategy that enhances students’ cognitive activity and fosters the development of critical and creative thinking, problem-solving skills, and metacognitive abilities. Key pedagogical conditions are identified, such as the transformation of the teacher’s role into that of a facilitator and the integration of modern educational technologies (project-based learning, case method, facilitation sessions). Prospects for further research include the development of assessment tools and the study of facilitation in digital learning environments.